Internet of Smart Clothing : Recognizing and Exploiting the Opportunities Introduced by Fashion 4.0 - Patwary, Ferdous Alam (2022)
Fashion industry has been influenced by recent technological revolution which has directed many organizations to encounter digitalization in almost every aspect of the business. The terms Fashion 4.0 and internet of smart clothing occurred because of digitalization and several market potentials has emerged due to the disruption introduced by the technologies related to these concepts. The thesis objective is to investigate how Fashion 4.0 and smart clothing are perceived, what market opportunities appears for the technologies and what understanding exists in recognizing and exploiting these potentials. These issues were addressed and explored by analysing 11 clothing and apparel companies of Finland and for this purpose in-depth interview with entrepreneurs, top managers, and marketing specialist along with 4 experts from three educational and one fashion research institute were conducted. A qualitative approach in the form of thematic analysis was adopted to analyse the data accumulated through interviews. The results suggests that the perception of Fashion 4.0 is understood as ‘digitalization' of fashion industry and smart garment is perceived as a functional fashion apparel not as a luxury aesthetic clothing. The opportunities that emerged due to the disruption revolves around different industry level encompassing, manufacturing, supply chain, distribution, and retail whereas intelligent garments have numerous market potentials in health, sports, entertainment and workwear industry. Social capital, earlier knowledge about technology and market and actively scanning the environment acted as primary antecedent in identifying the opportunities whereas technological and financial capabilities are revealed important in exploiting the potentials. This study benefits fashion entrepreneurs in discovering the unidentified potentials of smart clothing and technologies related to intelligent garments as well as offer actionable advice for mangers, designers and technology developers and finally several recommendations have been provided for future research.